Innovative Nanomedicine Delivery: Targeting Tumor Microenvironment to Defeat Drug Resistance - Wenjun Meng; Li Huang; Jiamin Guo; Qing Xin; Jiyan Liu; Yuzhu Hu (Pharmaceutics)
Nanodrug delivery systems have revolutionized tumor therapy like never before. By overcoming the complexity of the tumor microenvironment (TME) and bypassing drug resistance mechanisms, nanotechnology has shown great potential to improve drug efficacy and reduce toxic side effects. This review examines the impact of the TME on drug resistance and recent advances in nanomedicine delivery systems to overcome this challenge. Characteristics of the TME such as hypoxia, acidity, and high interstitial pressure significantly reduce the effectiveness of chemotherapy and radiotherapy, leading to increased drug resistance in tumor cells. Then, this review summarizes innovative nanocarrier designs for these microenvironmental features, including hypoxia-sensitive nanoparticles, pH-responsive carriers, and multifunctional nanosystems that enable targeted drug release and improved drug penetration and accumulation in tumors. By combining nanotechnology with therapeutic strategies, this review offers a novel perspective by focusing on the innovative design of nanocarriers that interact with the TME, a dimension often overlooked in similar reviews. We highlight the dual role of these nanocarriers in therapeutic delivery and TME modulation, emphasize their potential to overcome drug resistance, and look at future research directions.